Development and Optimization of RP-UHPLC Method for Mesalamine Through QbD Approach - Shill, Diponkor Kumar; Kumar, Uttom; Al Hossain, ASM Monjur; Rahman, Md Rezowanur; Shamsur Rouf, Abu Shara (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The current study aimed at developing and optimizing a prompt, simple and efficient RP-UHPLC method based on Quality by Design (QbD) for analyzing mesalamine. Experimental design for developing the method was performed capitalizing a 32 full factorial design in Design Expert® software (Version 12, Stat-Ease Inc., USA) where the percentage of methanol in the mobile phase and flow rate of the mobile phase were considered as independent factors and studied at three levels. Retention time, tailing factor and theoretical plate count were recorded as responses to the experiment. Mesalamine was analyzed using a reversed-phase C18 column (5μm, 150 ×4.6 mm) supported by a photodiode array plus (PDA+) detector with detection at 214 nm. The optimized method involved the use of a mobile phase of pH=7.4 phosphate buffer: methanol (63.5: 36.5, v/v) and a flow rate of 1.1 ml/min. Responses recorded during experimentation exhibited an error of -0.24%, 0.376% and -0.659% from predicted values of retention time, tailing factor and theoretical plate count, respectively. Experimental models adopted for the development of the method were found statistically significant (p-value <0.05). According to ICH Q2 (R1) guidelines, the method was also found to be robust, highly sensitive, specific, accurate, precise and linear. Dhaka Univ. J. Pharm. Sci. 21(1): 77-84, 2022 (June)